Distributed containment control and state observer design for multi-agent robotic system. (2015) - Shao, Nuan; Li, Huiguang; Wu, Xueli; Li, Guoyou
Aiming at the distributed containment control problem for multi-agent robotic system with stationary leaders, a position-sensorless control strategy is proposed based on binocular visual servo and feedback dissipative Hamilton theory. Firstly, the topological relationship among the robots is built by using directed graph, which makes each follower determine its neighbour robots. Secondly, a binocular visual servo model is established, so as to describe the dynamic information of the tracking target point for each follower through the neighbour robots' image information. Thirdly, the distributed containment controllers are designed based on the pre-feedback control strategy and feedback dissipative Hamilton theory; furthermore, in the case that each follower is not equipped with internal position sensor, the full-order state observers are developed by using the 'expansion + feedback' method, and then realise the position-sensorless control. Finally, a simulation is carried out on multiple two degrees-of-freedom (DOF) robots, and results show the validity of the proposed control strategy.